Weed dynamics, yield, quality and root growth of capsicum under drip irrigation and mulching (SAARC Journal of Agriculture, 2014)
A field experiment was conducted during 2006-07 and 2007-08 at Precision Farming Development Centre, Horticulture Farm, Indira Gandhi Agricultural University, Raipur, Chhattisgarh, India to evaluate the weed dynamics, yield, quality, organoleptic parameters and root growth of Capsicum as influenced by drip irrigation and mulches. The black polythene mulch being at par with paddy straw mulch gave the least weed population, dry weight and highest weed control efficiency over other mulches. Drip irrigation at 0.6 Epan obtained the least value of weed growth and highest weed control efficiency. Drip irrigation at 1.0 Epan showed highest fruit yield (32.02 t ha-1), total soluble solid (5.72), ascorbic acid (120.25 mg 100g-1) and organoleptic parameters but root growth registered maximum in flood irrigation at 1.0 IW/CPE. Black polythene followed by paddy straw mulch showed maximum fruit yield and other parameters. Pungent test scored maximum with flood irrigation at 1.0 IW/CPE and no mulch. Drip irrigation at 1.0 Epan along with black polythene as well as paddy straw mulch restrict weed growth, harvested quality fruit with higher fruit yield of capsicum. DOI: http://dx.doi.org/10.3329/sja.v10i2.18325 SAARC J. Agri., 10(2): 71-82 (2012)